Mathematics teacher knowledge in Iceland : historical and contemporary perspective - Kristín Bjarnadóttir (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 The history of mathematics education in Iceland in the 20th century reveals different opinions on the content of mathematics education of teachers and their knowledge.